Association of vitamin D level with systemic lupus erythematosus: A case-control study - Saha, Mrinal; Deb, Aparana; Sultan, Imtiaz; Razzaque, Md Abdur; Mahmud, Sakit; Rahul, Abu Kamran; Hassan, Khaled; Paul, Sujat (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune connective tissue disease. SLE patients are more prone to vitamin D deficiency because of their light sensitivity, renal involvement, and prolonged steroid use. This current study aimed to determine the relationship between vitamin D deficiency and SLE. Methods: In this case-control study, 50 SLE patients (cases) and 50 healthy people (controls) were recruited. The reference value of vitamin D is as follows: normal ≥ 30 ng/ml, deficient ≤ 20 ng/ml, and insufficient 21–29 ng/ml. Results: The mean (standard deviation) of vitamin D levels in SLE patients was 19.5 (5.3) ng/mL, which was significantly lower than those in healthy controls, 27.3 (10.0) ng/mL (P<0.001). The healthy controls had a higher proportion of people with normal vitamin D levels (≥ 30 ng/ml). We noticed a moderate negative correlation between vitamin D levels and fatigability, while a moderate positive correlation was seen with hemoglobin levels and the duration of sun exposure. However, in multiple logistic regression analysis, all the associations mentioned above disappeared. Conclusion: Although vitamin deficiency was found to be associated with SLE, its relationship disappears when the confounding by other variables is considered in the analysis.